Peter Fischli, David Weiss - How to work better - Spector, Nancy 1959-; Trotman, Nat (DelMonico Books, Prestel, 2016)
Throughout the course of their collaboration, Peter Fischli and David Weiss celebrated the sheer triviality of everyday existence, observing the world with bemused detachment. As this book shows, their often humorous work offers a sustained reflection on the intertwined strands of leisure, productivity and playful absurdity that shape our lives. With its deliberately mundane subject matter and quotidian source material, their work explores the poetics of banality in a wide range of mediums, including photography, videos, slide projections, films, books, sculptures and multimedia installations. This retrospective volume features an in-depth, illustrated survey of the artists' long history of collaboration, from the early Sausage Series (1979)-staged vignettes created in miniature using deli meats and various household items-to their last work, the large-scale public installation Rock on Top of Another Rock (2010-13), augmented by archival images, notes on process and interview excerpts culled from the artists' Zurich-based archives. A series of probing essays on their practice and thematic concerns rounds out this definitive account of Fischli and Weiss's vital contribution to contemporary art. Exhibition: Solomon R. Gugenheim Museum, New York, USA (05.02-20.04.2016)